Actuating Berbasis Motivasi Spiritual dalam Meningkatkan Loyalitas Karyawan Kafe Pena Rasa - Nur Rizkiyah Ramadhani; Zahra Jannatul Fidausi; Fina Rohmatika; Fidya Puji Ramadhani; Ahmad Amirul Aziz; Siti Zubaidah (Faculty of Economics and Business Universitas Dian Nuswantoro, 2025)
This study aims to examine the application of spiritual motivation-based actuating in increasing employee loyalty at Kafe Pena Rasa, an SME near Trunojoyo University Madura. Using a descriptive qualitative case study approach, data were collected through interviews, observations, and documentation. The results show that despite limited resources, low wages, and indirect supervision—conditions that usually cause high employee turnover—employees remain loyal. This loyalty is built through spiritual practices by instilling the intention to work as a form of worship, providing prayer facilities, closing on Fridays, a family culture, and an Islamic work ethic such as muraqabah. This fosters affective loyalty based on emotional bonds and value alignment rather than transactional loyalty based on salary. From the discussion results, it can be concluded that the application of actuating based on spiritual motivation at Kafe Pena Rasa contributes significantly to increasing employee loyalty, even though this effort is still relatively new and faces resource constraints. Therefore, spiritual motivation can be used as an alternative strategy in human resource management in the MSME sector, especially when financial support and material compensation are still limited. Penelitian ini bertujuan mengkaji penerapan actuating berbasis motivasi spiritual dalam meningkatkan loyalitas karyawan di Kafe Pena Rasa, UMKM di sekitar Universitas Trunojoyo Madura. Dengan pendekatan kualitatif deskriptif studi kasus, data dikumpulkan melalui wawancara, observasi, dan dokumentasi. Hasil menunjukkan bahwa meski sumber daya terbatas, upah rendah, dan pengawasan tidak langsung kondisi yang biasanya menyebabkan turnover tinggi karyawan tetap loyal. Loyalitas ini dibangun melalui praktik spiritual dengan menanamkan niat bekerja sebagai ibadah, menyediakan fasilitas salat, menutup saat Jumat, budaya kekeluargaan, dan etos kerja Islami seperti muraqabah. Hal ini menumbuhkan loyalitas afektif berdasarkan ikatan emosional dan keselarasan nilai bukan loyalitas transaksional berbasis gaji. Dari hasil pembahasan, dapat disimpulkan bahwa penerapan actuating berbasis motivasi spiritual di Kafe Pena Rasa memberikan kontribusi nyata dalam meningkatkan loyalitas karyawan, meskipun usaha ini masih tergolong baru dan menghadapi keterbatasan sumber daya sehingga motivasi spiritual dapat dijadikan strategi alternatif dalam pengelolaan sumber daya manusia pada sektor UMKM, khususnya ketika dukungan finansial maupun kompensasi material masih terbatas.